The Effectiveness of the CIRC Learning Model in terms of Self Confidence and Mathematical Generalization Ability - Budi Cahyono; Rina Dwi Setyawati; Alicia Indah Ardiani; Dyan Falasifa Tsani; Budi Waluyo; Kartono Kartono (Universitas Negeri Semarang, 2022)
Abstrak. This study aims to find out that the Cooperative Integrated Reading and Composition (CIRC) learning model is effective against self-confindence and mathematical generalist abilities of students in the material and ranks of class X TKJ SMK Mutiara Mayong. The population in this study were all students of class X TKJ SMK Mutiara Mayong. The sample of this study was class X TKJ 2 and X TKJ 3 which were randomly selected from three classes, each of which had 27, 18 and 23 students. The instrument used to collect data was a mathematical generalization ability test in the form of 5 problem descriptions and a self-confidence questionnaire consisting of 38 questions. Testing the effectiveness of Cooperative Integrated Reading and Composition (CIRC) learning models is carried out with a one sample t-test to determine whether there is an increase in students' generalization and self-confidence abilities between experimental classes before and after treatment is given. Meanwhile, to test whether there are differences in mathematical generalization abilities and students' self-confidence between the experimental class and the control class, a t-independent test is performed. The results showed that (1) effective Cooperative Integrated Reading and Composition (CIRC) learning model in terms of students 'self-confidence, (2) Cooperative Integrated Reading and Composition (CIRC) learning model effectively in terms of students' generalization abilities.